Therapeutic potential of stem cell-derived extracellular vesicles in osteoarthritis: preclinical study findings - Ki Hoon Kim (Laboratory Animal Research, 2020)
Abstract Extracellular vesicles (EVs) are nano-sized particles secreted by almost all cell types, and they mediate various biological processes via cell-to-cell communication. Compared with parental cells for therapeutic purposes, stem cell-derived EVs have several advantages such as reduced risk of rejection, less oncogenic potential, ease of long-term storage, lower chance of thromboembolism, and readiness for immediate use. Recent studies have demonstrated that EVs from stem cells, mostly from mesenchymal stem cells (MSCs) from various tissues, have anti-inflammatory, anti-oxidative, anti-apoptotic, and proliferative role in injured organs including osteoarthritic lesions. Herein, we provide a review about the up-to-date studies in preclinical application of stem cell-derived EVs in osteoarthritis animal arthritis models.